Kesan penyederhanaan kepemimpinan transformasional dan budaya masyarakat terhadap hubungan antara budaya organisasi dengan perubahan : Kajian institut pengajian tinggi swasta di Jakarta - Sugiana, I Wayan (2022)
The purpose of this study was to determine how much influence organizational culture (X1) has on organizational change (Y) with transformational leadership (X2) and community culture (X3) as moderating factors. Using a descriptive quantitative methodology with SmartPLS 3.0 data analysis, a population of 315 higher education institution leaders in Jakarta with a sample of 181 higher education institutions were selected. The research question wants to know whether there is a) the influence of organizational culture on organizational change, b) the influence of transformational leadership on organizational change, c) the influence of community culture on organizational change, d) the extent of the influence of transformational leadership moderation on the relationship of organizational culture and organizational change, and e) the extent to which the influence of community culture moderation on the relationship of organizational culture and organizational change. Based on the data description, respondents' answers to the questionnaire, reliability test, composite reliability, validity test, convergent validity, discriminant validity and analysis of the best PLS model, it was found that: 1) organizational culture variable has a positive and significant influence on organizational change by 7, 1%, relatively small, 2) transformational leadership variable has a positive and significant influence on organizational change of 88.89%, relatively hight, 3) community cultural variable has a positive and significant influence on organizational change of 5.3%, relatively small, 4) the moderation influence of transformational leadership does not moderate the relationship between organizational culture and organizational large, and 5) the moderation influence of community culture does not moderate the relationship between organizational culture and organizational change. Thus these two moderation variables do not strengthen or weaken. Both can independently have a direct influence on organizational change and do not require moderation to organizational culture for the purpose of organizational change. Finally, this study found empirically and scientifically that transformational leadership variables has the largest and strongest influence on organizational change of private higher education institutions in Jakarta. The suggestion to higher education institution leaders is to strengthen the formation of a dominant organizational culture by conducting real and low-cost activities such as outbound and joint sports. In a rapidly changing situation like today, a transformative leader is needed who is also able to anticipate the dynamic cultural changes of society.